Youth baseball pitching mechanics: A systematic review - Thompson, S. F.; Guess, T. M.; Plackis, A. C.; Sherman, A. L.; Gray, A. D. (Sports Health: A Multidisciplinary Approach, 2018)
Context: Pitching injuries in youth baseball are increasing in incidence. Poor pitching mechanics in young throwers have not been sufficiently evaluated due to the lack of a basic biomechanical understanding of the "normal" youth pitching motion. Objective: To provide a greater understanding of the kinetics and kinematics of the youth baseball pitching motion. Data Sources: PubMed, MEDLINE, and SPORTDiscus databases were searched from database inception through February 2017. Study Selection: A total of 10 biomechanical studies describing youth pitching mechanics were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: Manual extraction and compilation of demographic, methodology, kinetic, and kinematic variables from the included studies were completed. Results: In studies of healthy youth baseball pitchers, progressive external rotation of the shoulder occurs throughout the start of the pitching motion, reaching a maximum of 166° to 178.2°, before internally rotating throughout the remainder of the cycle, reaching a minimum of 13.2° to 17°. Elbow valgus torque reaches the highest level (18 ± 4 N·m) just prior to maximum shoulder external rotation and decreases throughout the remainder of the pitch cycle. Stride length is 66% to 85% of pitcher height. In comparison with a fastball, a curveball demonstrates less elbow varus torque (31.6 ± 15.3 vs 34.8 ± 15.4 N·m). Conclusion: Multiple studies show that maximum elbow valgus torque occurs just prior to maximum shoulder external rotation. Forces on the elbow and shoulder are greater for the fastball than the curveball.